The impact on undergraduate students - Reenie Tian; Kamna Kalkunte; Esha Pia; Gianna Dunn; Nina Bugg; Mayank Chugh (eLife)
Anti-science policies, funding cuts, scientific censorship and the US withdrawing from international commitments are worrying members of the ReForm Lab at the College of William & Mary.